Norwegian Priority Setting in Practice - an Analysis of Waiting Time Patterns Across Medical Disciplines - Jurgita Januleviciute Gangstøe; Torhild Heggestad; Ole Frithjof Norheim (Kerman University of Medical Sciences, 2016)
Background: Different strategies for addressing the challenge of prioritizing elective patients efficiently and fairly have been introduced in Norway. In the time period studied, there were three possible outcomes for elective patients that had been through the process of priority setting: (i) high priority with assigned individual maximum waiting time; (ii) low priority without a maximum waiting time; and (iii) refusal (not in need for specialized services). We study variation in priority status and waiting time of the first two groups across different medical disciplines. Methods: Data was extracted from the Norwegian Patient Register (NPR) and contains information on elective referrals to 41 hospitals in the Western Norway Regional Health Authority in 2010. The hospital practice across different specialties was measured by patient priority status and waiting times. The distributions of assigned maximum waiting times and the actual ones were analyzed using standard Kernel density estimation. The perspective of the planning process was studied by measuring the time interval between the actual start of healthcare and the maximum waiting time. Results: Considerable variation was found across medical specialties concerning proportion of priority patients and their maximum waiting times. The degree of differentiation in terms of maximum waiting times also varied by medical discipline. We found that the actual waiting time was very close to the assigned maximum waiting time. Furthermore, there was no clear correspondence between the actual waiting time for patients and their priority status. Conclusion: Variations across medical disciplines are often interpreted as differences in clinical judgment and capacity. Alternatively they primarily reflect differences in patient characteristics, patient case-mix, as well as capacity. One hypothesis for further research is that the introduction of maximum waiting times may have contributed to push the actual waiting time towards the maximum. The finding that the actual waiting time was very close to the maximum waiting time supports this. The lack of clear correspondence between the actual waiting time for patients and their priority status may imply that urgency, described in the referral letter, and severity of illness, according to guidelines, are two separate entities.